STRATEGI BERTAHAN INDUSTRI MAKANAN SKALA KECIL PASCA KENAIKAN HARGA PANGAN DAN ENERGI DI KOTA YOGYAKARTA - Y. Sri Susilo (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
The purpose of this research is to identify and analyze the strategy of surviving performed by small-scale food industry against the raise of food and energy price in Yogyakarta. The definition of small industry is the business that performed production activity with numbers of production labor 1 – 19 persons. Sample size is 100 respondents. Method of sampling utilizes convenience sampling. Primary data is compiled by interview based on given questionnaires. Besides that, in-depth interview also performed to get more detailed information. Secondary data is obtained from related agencies, and browsing on internet. Data analyzed with descriptive approach. The result shows that all respondent is keeping the production survive and the business runs. Strategy that performed by respondents in order to survive is varied depend on the kind of product and the condition of each respondent’s business. The strategy of surviving that is performed is: (1) raising the sell price and (2) not raising the price or price is fixed. Both chosen strategy is combined with strategy: (1) reducing the profit margin and (2) reducing the product size. Another applied strategy is performed efficiency by pressing the promotion cost and the costs that social-related, like several donations for societies around.